PENGARUH ALOKASI PAJAK ANTAR PERIODE, PERSISTENSI LABA, PROFITABILITAS, DAN LIKUIDITAS TERHADAP KUALITAS LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEITahun 2012-2016) - Reza Ardianti (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study was to describe (1) the effect of inter-period tax allocations on earning quality, (2) the effect of earnings persistence on earning quality, (3) the effect of profitability on earning quality, and (4) the effect of liquidity on earning quality. This study classified as a causative research. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in periode 2012 to 2016. Sample was determined by purposive sampling, there are 49 manufacturing companies. The data is secondary. Data was collected by IDX: www.idx.co.id and obtained from the website: www.yahoofinance.com. Analysis of the data was use as multiple linear regression by the R square, F test, t test, and the classical assumption test of normality test, multicollinearity test, and heteroscedasticity test. The results that (1) inter-period tax allocations is not effect the quality of earningwith level significant 0,127 and β is 0,005,(2) earnings persistence is not effect the quality of earning with level significant 0,514 and β is 0,000, (3) the profitability is significant positive on the earning quality with level significant 0,001 and β is 0,001, and (4) the liquidity is significant negative on the earning quality with level significant 0,006 and β is -0,002. Keyword: Earning quality, inter-period tax aloocations, earnings persistence, profitability, liquidity